The third sector delivery of social services: needs, effectiveness and strategies for improvement - Bach-Mortensen, A (2020)
Background The third sector is expanding and becoming a bigger provider of public, social and health care services. However, little research has been undertaken to date to evidence the ability of third sector organisations (TSOs) as substitute health and social care providers to work effectively and in accordance with evidence-based practice (EBP). This entails having established processes for monitoring service delivery and outcomes, and including relevant stakeholders with the best available evidence in decision-making processes. Whilst the principles of EBP are gradually becoming an accepted part of practice in health and social care settings, little is known about how these principles have transferred into the third sector. To meet the growing demand on health and social care as a result of changes such as ageing populations, such services are increasingly delivered in quasi-markets, which are markets where public, for-profit, and third sector providers compete for service contracts financed by the state. Research convention and theories on the typology of sector have long contended that organisations across sector are driven by different incentives, but it remains unclear how, if at all, sector specific traits influence service quality. Further, little research has investigated the implications associated with the use of quasi-markets and whether certain types of service providers deliver systematically higher value than others. Objectives This thesis aims to inform these areas by conducting two systematic reviews, which will be operationalised as an evaluation of the factors influencing the ability of TSOs to (1) evaluate their activities and (2) implement evidence-based interventions. (3) The thesis then tests whether quality-related outcomes vary across for-profit, public and third sector organisations in the context of social care organisations in Scotland. These three pieces of research have been developed and written as stand-alone journal articles for publication, bookended by chapters that will engage in a broad discussion of the core issues on the topic and of the core research questions. Together, these three papers provide an important and novel contribution to the existing literature by identifying, appraising, and synthesising existing research on the evaluation and delivery issues of TSOs, while also empirically exploring whether quality outcomes differ across public, for-profit, and third sector social care providers. Methods A variety of methods are employed throughout the thesis. Papers 1 and 2 are systematic reviews conducted following best practice and in line with PRISMA guidelines. Both reviews included systematically searching key databases using relevant search strings, contacting experts, and reviewing websites. All included literature was quality appraised and synthesised using thematic analysis. Paper 3 employed generalised ordered logit models utilising data from the Care Inspectorate (the independent regulator of care services in Scotland) to test whether service- related outcomes vary across for-profit, public and third sector organisations. All papers were reported following best practice guidelines. Results Paper 1 identified the main barriers for TSOs undertaking evaluation to be related to the lack of financial resources, lack of technical capability and evaluation literacy, and challenges around identifying relevant evaluation systems and outcome indicators. Key facilitating factors involved securing the appropriate support and having an organisational culture that supports evaluation, in addition to the motivation to be accountable to stakeholders. This paper has been published in Systematic Reviews. Paper 2, which focused on factors influencing the ability of TSOs to implement evidence-based interventions (EBIs), identified resource limitations, in particular staff and finance, to be the most reported barrier to TSOs implementing EBIs. Organisational culture, including factors such as alignment between the mission of the TSO and EBI, and support/prioritisation of the implementation process, were the most reported facilitators. This paper has been published in Implementation Science. Paper 3 found that public and third sector social care providers were generally more likely to be rated of high quality and of lower risk, compared to for-profit organisations, which were more likely to be rated of adequate quality and of higher risk. This paper has been published in BMJ Open. Discussion The findings of these three studies suggest that from a regulation perspective, the large range of different activities within the third sector makes it challenging to develop policies that are appropriate to all types of TSOs. While policy-makers and academics continue to emphasise the importance of the third sector in alleviating social issues, TSOs are subject to little and insufficient guidance and support on how to evaluate and implement their services in accordance with best practice. This lack of clarity and support regarding how TSOs should adhere to best practice is problematic and may largely be at the expense of the beneficiaries; most of whom include vulnerable population groups. The findings presented in this thesis constitute a novel contribution to the knowledge-base regarding the current state of affairs in the third sector delivery of health and social care services, and also informs theories on the typology of sector. However, the findings should be interpreted with caution as a result of the study limitations, which are discussed in full. Further, the practical and policy implications identified in each paper provide an important resource for key stakeholders in terms of future strategies for regulation and improved guidance/support. As such, the findings do not just have academic relevance in terms of improving the evidence-base with regard to existing evaluation, implementation and quality practices among TSOs, but also inform practice in terms of current debates about how the needs of TSOs can be met going forward.